The Effect of the Proportion of Moringa Leaves on the Acceptance of Chicken Dumplings - retno puspita sari; Arya Ulil Albab (Universitas Muhammadiyah Sidoarjo, 2020)
Indonesia is in the tropical region so there are a lot of biodiversities. One of the diversities is the Moringa plant. Moringa plant contains a lot of micronutrient values including some vitamins, minerals and bioactive compounds in the form of chlorophyll. Micronutrients play a role in the formation of hormones, regulating the immune system and enzyme activity. Bioactive compounds found in Moringa leaves act as antioxidants that can ward off free radicals. The purpose of this research is to analyze the organoleptic acceptance of chicken dumplings by the addition of Moringa leaves as a functional food. This study uses a pure experimental method with a Completely Randomized Design and there are 3 groups namely P1 (without the addition of Moringa leaves), P2 (addition of Moringa leaves 0.5%) and P3 (addition of Moringa leaves 1%) with each group applying 3 replications. Statistical analysis of the organoleptic test uses Friedman rank. The highest mean rank value among the three groups for the four parameters is in P2, i.e. for the parameters of color (2.51), aroma (2.43), texture (2.51), and taste (2.48). The best percentage of acceptance in color (P2 = 81%), aroma (P2 = 81%), texture (P2 = 74%), and taste (P2 = 77%). It can be concluded that in group 2 (giving Moringa leaves with the proportion of 0.5%) is the most preferred by panelists from the four organoleptic test elements (color, aroma, texture, and taste). The acceptance value of texture and taste is still below 80% so it is necessary to modify the recipe to get optimal organoleptic results.